KONSEP-KONSEP DASAR MATEMATIKA DALAM EKONOMI - Abdan Matin Ahmad (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2021)
The basic concepts of mathematics in economics are important materials in learning economics mathematics. This study aims to examine the basic concepts of mathematics in economics as a support and reference in learning activities. The method used in the study used a literature review study. Based on the studies carried out there are six subjects of basic mathematical concepts in economics, namely: 1) variables, constants, coefficients, and parameters, 2) equations and inequalities, 3) set concepts and theory, 4) real number systems, 5) rules exponents, roots, factoring, and 6) fractions, decimals and percentages.